Discourse analysis of online media on the haze disaster due to forest fires in Jambi, Indonesia - Galuh Pratama Jati; Rahmawati Husein (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
Forest fire–induced haze remains a recurring ecological crisis in Indonesia, yet limited attention has been given to how online media frame local government responses and shape public understanding of such disasters. This study aims to analyze the portrayal of the Jambi local government in online media coverage of the haze crisis, with a particular focus on crisis management narratives and the representation of key actors involved. Using a qualitative descriptive approach, this research employs NVivo 12 Plus to conduct a discourse-oriented analysis of news articles published by four major Indonesian online media outlets—Detiknews.com, Kompas.com, CNNIndonesia.com, and Liputan6.com. The findings reveal that the haze disaster in Jambi was predominantly framed through five key sectors: education, transportation, economy, environment, and health. Liputan6.com emphasized environmental and economic impacts, Kompas.com focused primarily on health-related issues, Detiknews.com highlighted educational disruptions, and CNNIndonesia.com concentrated on public health concerns. Across all platforms, the haze crisis was consistently framed as a provincial emergency caused by forest and land fires, with frequent emphasis on deteriorating air quality and the involvement of cross-sector actors in disaster response policies. This study contributes to media discourse analysis by demonstrating how sector-specific framing creates fragmented narratives that may influence public perception and policy prioritization in local disaster governance.